Reconstruction of the original mycoflora in pelleted feed by PCR‐SSCP and qPCR. Issue 2 (21st August 2014) - Dorn‐In, Samart; Fahn, Carmen; Hölzel, Christina S.; Wenz, Sebastian; Hartwig, Isabella; Schwaiger, Karin; Bauer, Johann
Abstract Ground feeds for pigs were investigated for fungal contamination before and after pelleting (subsamples in total n = 24) by cultural and molecular biological methods. A fungal‐specific primer pair ITS1/ITS5.8R was used to amplify fungal DNA; PCR products were processed for the PCR‐SSCP method. In the resulting acrylamide gel, more than 85% of DNA bands of ground feeds were preserved after pelleting. Twenty‐two DNA bands were sequenced; all represented fungal DNA. The level of fungal DNA in ground feed samples was equivalent to 4.77–5.69 log10 CFU g−1, calculated by qPCR using a standard curve of Aspergillus flavus. In pelleted feed, the level of fungal DNA was in average ± 0.07 log10 different from ground feed. Quantified by cultural methods, the fresh ground feeds contained up to 4.51 log10 CFU g−1 culturable fungi, while there was < 2.83 log10 CFU g−1 detected in pelleted feeds. This result shows that, while the process of pelleting reduced the amount of living fungi dramatically, it did not affect the total fungal DNA in feed. Thus, the described methodology was able to reconstruct the fungal microbiota in feeds and reflected a considerable fungal contamination of raw materials such as grains.